Recent advances in smart hydrogels for biomedical applications: From self-assembly to functional approaches - Ferreira, N. N. [UNESP]; Ferreira, L. M.B. [UNESP]; Cardoso, V. M.O. [UNESP]; Boni, F. I. [UNESP]; Souza, A. L.R. [UNESP]; Gremião, M. P.D. [UNESP] (Elsevier, 2018)
This review discusses basic aspects used to control the architecture and functional properties of smart hydrogels. The introduction briefly outlines what has been accomplished regarding smart hydrogels and explores historical aspects and the fundamental understanding of these systems. Then, a short discussion on the chemical interactions and the main variables involved in architectural construction is exhibited. Further analysis provides the basis for optimizing biological responses through system modulation. Finally, we outline perspectives and challenges for building smart hydrogels into functionalized and modulated delivery systems.
Keywords: Drug delivery systems; Dynamic interactions; Functional approach; Functional biomaterials; Responsiveness; Smart hydrogels